Simultaneous co-doping of RuO2 and IrO2 into anodic TiO2 nanotubes: A binary catalyst for electrochemical water splitting. (9th March 2017) - Yoo, Hyeonseok; Oh, Kiseok; Lee, Yu Ri; Row, Kyung Ho; Lee, Gibaek; Choi, Jinsub
Abstract: The simultaneous doping of RuO2 and IrO2 catalysts into anodic TiO2 nanotubes (NTs) was successfully achieved by single-step anodization. KRuO4 was used as the precursor for the RuO2 dopant. However, for IrO2 doping, IrOx nanoparticles (NPs) were synthesized from IrCl3 as an intermediate species to avoid damage to the NTs by chloride ions during doping. IrO 4 − generated from the IrOx NPs through selective dissolution in the electrolyte was simultaneously doped into the positively biased TiO2 NTs along with RuO2 . The structural features, NT length, and amount of catalyst doping were controlled by the concentration of HF in the electrolyte and the anodizing time. The binary-catalyst-doped TiO2 NTs exhibited an outstanding onset potential of 0.84 V for the oxygen evolution reaction (OER). In addition, the amount of O2 gas evolved during the OER at 2.0 V was measured to be 230 μmol cm −2  min −1 by gas chromatography, which corresponds to a faradaic efficiency of 99%. The major oxidation states of the metals in the catalysts were found to be Ru 4+ and Ir 4+ by X-ray photoelectron spectroscopy and transmission electron microscopy selected area electron diffraction analysis, indicating the presence of RuO2 and IrO2 in the TiO2 NTs. Graphical abstract: Binary catalysts are successfully doped into TiO2 nanotubes by single-step anodization process for OER application. Highlights: TiO2 nanotubes (NTs) including dopants of IrO2 and RuO2 are prepared by single-step anodization. The rutile phase of IrO2 and RuO2 is shown into the crystalline TiO2 with even distribution. The maximum current density of 94 mA cm −2 is achieved from the IrO2 –RuO2 doped TiO2 NTs for OER performance. The evolved oxygen gas amount of 230 μmol exhibits 99% of faradaic efficiency.